2020
DOI: 10.26434/chemrxiv.12906551
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Volatile Signal Controls Virulence in the Plant Pathogen Pseudomonas syringae pv. syringae and a Strategy for Infection Control in Organic Farming

Abstract: <div><div><div><p>Pseudomonas syringae is an important pathogen of many agriculturally valuable crops. Among the various pathovars described P. syringae pv. syringae (Pss) has a particularly wide host range, infecting primarily woody and herbaceous host plants. The ability of Pss to cause bacterial apical necrosis of mango trees is dependent on the production of the antimetabolite toxin mangotoxin. The production of this toxin was shown to be regulated by a self-produced signaling molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Based on the homology observed among ham operons, it was suggested that members of the genera Pseudomonas , Pandorea, and Burkholderia may use the diffusible signal molecule—valdiazen (valinol diazeniumdiolate), which autoregulates its own biosynthesis and also of fragin. Fragin is a metallophore and its metal chelating ability is responsible for its antifungal property [ 184 , 185 , 186 ].…”
Section: Other Potential Qs Signalsmentioning
confidence: 99%
“…Based on the homology observed among ham operons, it was suggested that members of the genera Pseudomonas , Pandorea, and Burkholderia may use the diffusible signal molecule—valdiazen (valinol diazeniumdiolate), which autoregulates its own biosynthesis and also of fragin. Fragin is a metallophore and its metal chelating ability is responsible for its antifungal property [ 184 , 185 , 186 ].…”
Section: Other Potential Qs Signalsmentioning
confidence: 99%
“…A second more realistic possibility is that the Pbo cluster is participating in the regulation of phaseolotoxin biosynthesis, particularly considering the complexity of the regulatory circuitry involved. This putative regulatory activity could then be similar to the regulation of the antimetabolite toxin mangotoxin by the volatile compound leudiazen, which belongs to the family of diazeniumdiolate communication molecules [ 37 ]. The biosynthesis of leudiazen requires the mgoBCAD operon, which consists of four genes coding for two predicted oxygenases, an NRPS and a putative polyketide cyclase/dehydratase [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The biosynthesis of leudiazen requires the mgoBCAD operon, which consists of four genes coding for two predicted oxygenases, an NRPS and a putative polyketide cyclase/dehydratase [ 38 ]. Besides mangotoxin biosynthesis, leudiazen also impacts virulence and likely other phenotypic traits, and this is likely the reason why homologs of the mgo operon are present in diverse pseudomonads and other bacteria [ 37 , 39 ]. Thus, it is conceivable that the putative secondary metabolite produced by the Pbo cluster is also a signaling molecule regulating phaseolotoxin biosynthesis; likewise, its potential implication in regulating other phenotypes would also explain the presence of the Pbo island in bacteria that do not synthesize phaseolotoxin.…”
Section: Discussionmentioning
confidence: 99%